Effect of mechanical mismatch on fracture mechanical behavior of SA 508 – Alloy 52 narrow gap dissimilar metal weld. (November 2017) - Sarikka, Teemu; Ahonen, Matias; Mouginot, Roman; Nevasmaa, Pekka; Karjalainen-Roikonen, Päivi; Ehrnstén, Ulla; Hänninen, Hannu
Abstract: In modern pressurized water reactor (PWR) designs, dissimilar metal welds (DMW) between the reactor pressure vessel (RPV) nozzles and safe-ends connected to the main coolant pipes are manufactured using a narrow-gap welding (NGW) technique. In addition to the new weld design, the filler metals have been changed from conventional Alloys 82 and 182 to higher Cr containing Alloys 52 and 152 to ensure the structural integrity of the welds during long term operation. The changes in weld design and filler metal have an effect on the mechanical mismatch state of the DMW which has an effect on the fracture behavior of the weld. For the experimental determination of the local strength variations and the fracture mechanical behavior of a modern NG-DMW, a weld mock-up consisting of SA 508 pressure vessel steel with AISI 309L/308L cladding, AISI 304 piping steel, and Alloy 52 weld metal was manufactured. The NG-DMW was characterized in both as-welded and post-weld heat treated (PWHT) conditions. The results showed that the highest strength mismatch existed between the carbon-depleted zone (CDZ) in the SA 508 heat-affected zone (HAZ) and the Alloy 52 weld metal. High fracture toughness values were observed for the different zones of the weld and the crack propagation occurred towards the softer SA 508 HAZ CDZ. Highlights: The strength mismatch state and the microhardness profile predict quite similar crack growth behavior. Microstructural characterization and nanoindentation reveal local narrow zones near the weld interface. These zones result in a high mismatch state near the fusion boundary. The fracture resistance was at its lowest at the fusion boundary and the PWHT decreased the fracture resistance. The mismatch state caused the crack to propagate towards the fusion boundary and in the CDZ of the SA 508 HAZ.